Planning the Design and Execution of Student Performance Assessment in Serious Games - Oliveira, Rháleff N. R.; Rocha, Rafaela V.; Goya, Denise H. (Journal on Interactive Systems, 2021)
Serious Games (SGs) are used to support knowledge acquisition and skill development. For this, there is a need to measure the results achieved (both during and after students play) to ensure the game effectiveness. In this context, the aim is to develop and evaluate the AvaliaJS, a conceptual model to structure, guide and support the planning of the design and execution of the student’s performance assessment in SGs. AvaliaJS has two artifacts: a canvas model, for high-level planning, and an assessment project document, for more detailed specifications of the canvas. To analyze and exemplify the use of the model, the artifacts were applied to three ready-made games as a proof of concept. In addition, the quality of AvaliaJS was evaluated by experts in SGs development and assessment using a questionnaire. The results of experts’ answers confirm a good internal consistency (Cronbach’s alpha α = 0.87) which indicates that AvaliaJS is correct, authentic, consistent, clear, unambiguous and flexible. However, the model will need to be validated during the process of creating a new game to ensure its usability and efficiency. In general, AvaliaJS can be used to support the team in the planning, documentation and development of artifacts and data collection in SGs, as well as in the execution of the assessment, learning measurement and constant and personalized feedback for students.